Deep Brain Stimulation - Chen, X.L. (S. Karger AG, 2013)
Deep brain stimulation (DBS) has provided remarkable therapeutic benefits for people with a variety of neurological disorders. Despite the uncertainty of the precise mechanisms underlying its efficacy, DBS is clinically effective in improving motor function of essential tremor, Parkinson's disease and primary dystonia and in relieving obsessive-compulsive disorder. Recently, this surgical technique has continued to expand to other numerous neurological diseases with encouraging results. This review highlighted the current and potential future clinical applications of DBS.